Pseudoaneurysm of dorsalis pedis artery following lisfranc surgery: a rare complication - Siti Munira SM,; Mohd Yazid Bajuri,; Naadira Faa’iza M,; Mohd Hezery H, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Aneurysm and pseudoaneurysm of the dorsalis pedis artery remains to be rare vascular entities with a reported incidence of 0.5% of peripheral arterial aneurysms. Only, few cases were reported. The formation of pseudoaneurysm is commonly associated with fracture, laceration wound or iatrogenic arterial injury. An arterial injury that coincides with pseudoaneurysm can initially be missed due to lack of clinical findings. Prompt recognition remains paramount to reduce morbidity and mortality. Here, we present a rare complication of a commonly performed orthopaedic procedure in a young male who presented with painful swelling over left foot after he was involved in an industrial injury. He presented again with a pulsating mass over his left foot after 2 months post fixation surgery of a Lisfranc injury. He was treated conservatively with compression bandage and able to regain to his normal activity after the treatment initiated.